2008
DOI: 10.1007/s12272-001-1139-9
|View full text |Cite
|
Sign up to set email alerts
|

β-secretase (BACE1) inhibitors from Perilla frutescens var. acuta

Abstract: In the course of screening for anti-dementia agents from natural products, two beta-secretase (BACE1) inhibitors were isolated from the methanolic extract of Perilla frutescens var. acuta and identified as luteolin (1) and rosmarinic acid (2) with IC50 values of 5.0 x 10(-7) M and 2.1 x 10(-5) M, respectively. They inhibited BACE1 in a non-competitive manner with a substrate in Dixon plots, suggesting that they might bind to either beta-secretase subsite or to another regulatory site. Kivalues of 1 and 2 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 32 publications
0
19
0
2
Order By: Relevance
“…In addition, luteolin and rosmarinic acid was identified as the active principles of β-secretase inhibition from Perilla frutescens var. acuta (Laminaceae) (Choi et al, 2008a).…”
Section: β-Secretase Inhibitorsmentioning
confidence: 99%
“…In addition, luteolin and rosmarinic acid was identified as the active principles of β-secretase inhibition from Perilla frutescens var. acuta (Laminaceae) (Choi et al, 2008a).…”
Section: β-Secretase Inhibitorsmentioning
confidence: 99%
“…3). So far, 13 of the components found within MLC601 have been found to have the ability to reverse and prevent events associated with Aβ-induced toxicity [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. Specifically, radix salviae miltiorrhizae, radix paeoniae rubrae, radix angelicae sinensis, radix astragali, rhizoma chuanxiong and Carthamus tinctorius have all been shown to ameliorate critical toxic events within the amyloid cascade hypothesis (fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although P. frutescens (L.) Britton var. acuta Kudo is known to contain various components, such as phenylpropanoids and terpenes (Fujita et al ., 1994; Liu et al ., 2000) and to possess various pharmacological actions including antidepressant-like effects (Nakazawa et al ., 2003) and β-secretase inhibiting activity (Choi et al ., 2008), the present study has clearly shown the importance of phenylpropanoids in expressing inhibitory activity against lung inflammation.…”
Section: Discussionmentioning
confidence: 99%